(untitled) (Journal of Computational Mathematics, 2018)
We construct a spectral-difference schemes for solving two-dimensional vorticity equation with a single periodical boundary condition. The conservation, the generalized stability and the convergence are proved. Both steady and unsteady problems are considered.